ORIGIN AND DYNAMICS OF FE AND MN SEDIMENTARY LAYERS IN LAKE BAIKAL - Granina L.; Müller B.; Wehrli B. (My University, 2004)
Remobilization and accumulation of iron and manganese were measured by porewater and sediment–core analyses at six contrasting sedimentary environments of Lake Baikal, with bulk sedimentation rates varying between 0.8 and 0.02 mm year⁻¹. The results allow for the distinction between two types of Fe and Mn diagenesis in areas of relatively high sedimentation and in regions of low sedimentation rates. In the first case, only small Fe/Mn enrichments near the sediment–water interface were observed in the central and southern basins, at the high sediment flux area near the Selenga Delta, and in Maloe More strait. Massive sedimentary layers enriched in Fe and Mn were found within the upper 15–25 cm of the sediments exclusively in Northern Baikal and in the underwater Academician Ridge, which are characterized by low sedimentation rates and deep sulfate penetration depths in the porewaters. The Mn content in the enriched layers ranged from 10⁻⁵ mol cm⁻² at the sites near the Selenga Delta up to 10⁻² mol cm⁻² at Academician Ridge. The accumulation times for the enriched Fe/Mn layers, calculated from the size of the Fe and Mn oxide pools and the diffusive fluxes into the enriched zones, also varied by a factor of 1000. They ranged from a few years near the Selenga Delta to several thousand years for the sites at Academician Ridge and Northern Baikal. These values were generally congruent with the sediment age of the accumulation zones calculated from sedimentation rates.